TANTANGAN KOPERASI MELALUI SOSIALISASI MASYARAKAT SEBAGAI UPAYA MEWUJUDKAN KESEJAHTERAAN ANGGOTA KOPERASI SELAMA PANDEMI COVID-19 DI ERA INDUSTRI 4.0 - Julia Muthiani; Arjuna Rizaldi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study aims to discuss how to overcome the challenges of cooperatives through community socialization as a form of seeking the welfare of cooperative members during the pandemic, especially industry 4.0, in which the authors use qualitative methods with the type of descriptive research discussed. The data collection procedure was carried out online by the author to the management of the PT X cooperative and several members of the PT X cooperative who were randomly selected to fulfill the research of this journal. In addition, the evaluation of the IT 4.0 challenges on the socialization of cooperatives to members aims to provide opportunities for the community to obtain economic stability for the feasibility of their daily lives.